Strategi Pengembangan Usaha Mikro Kecil Menengah (UMKM) Berbasis Ekonomi Kreatif Di Kabupaten Buton Selatan - Nining Asniar Ridzal; Ernawati Malik; I Wayan Sujana; Vivied Octaviani (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to identify and analyze creative economy-based micro, small and medium enterprise development strategies in South Buton district. This research was conducted on 99 MSMEs in 3 sub-districts. The analysis tool uses SWOT analysis. The results show that from the results of weighting and determining the strategy for culinary business in Tables 1, 2 and 3, it is known that the strength is 0.87, the weakness is 0.58, the opportunity is 4.25, the threat is 3.24, it can be concluded that for determining the strategy The main focus of the culinary sector is in quadrant 1, namely the culinary sector has strengths and opportunities with the main strategy, namely when businesses have strengths and can also see opportunities, what must be done is to be actively involved in activities carried out by the government related to culinary business. This is done to introduce our efforts to find new relationships for business development. From the results of weighting and determining the strategy for the handicraft business in Tables 1, 2 and 3 it is known that the strength is 1.2, the weakness is 0.66, the opportunity is 1.14, the threat is 0.50, it can be concluded for determining the main strategy for the handicraft business entered in quadrant 1, namely the craft sector has strengths and has opportunities with the main strategy, namely increasing creative craft branding through multimedia and social media.